BUFFALO SPERMATOZOA CLASSIFIED BASED ON PLASMALEMMA FUNCTIONAL INTEGRITY AND ACROSOMAL INTEGRITY TESTS - SELVARAJU, S; RAVINDRA, J P; PRATAP, N; PRASAD, B ARUN; RENUKARYADHYA, G J; ARORA, V K (The Indian Journal of Animal Reproduction, 2023)
The aim of this study was to assess the plasmalemma functional integrity and acrosomal integrityand their relationship with sperm functional tests in assessing buffalo semen quality. Fifty-two ejaculatesfrom thirteen Murrah buffalo bulls were used for the study. Plasmalemma integrity and acrosomalintegrity was assessed byfluorogenic and hypoosmotic swelling- Giemsa (HOS-G) test. The sampleswere classified into different subpopulations based on their reaction to fluorogenic staining and HOSGtest, respectively. No difference in plasmalemma integrity (%) was observed (49.11±2.53 vs.48.59±2.48) between fluorogenic and HOS-G tests. However, the acrosomal integrity(%) assessed byHOS-G test (82.43±4.15) was significantly higher (P
Keywords: Buffalo bull; Semen; Plasmalemma integrity; Acrosomal integrity